PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN JASA APOTEK FITRI TEMANGGUNG - FARRUK RASTHA PRADIPTA (Jurnal Manajemen, 2019)
ABSTRACTThis study aimed to see if there are service quality affects customer satisfaction in using the services of Pharmacy Fitri Temanggung. Subjects in this study is that consumers Pharmacy Fitri Temaggung aged 18-60 years; purchase drugs at private expense; able to read, write, and communicate well; and willing to fill out a questionnaire. The samples used in this study was 116 subjects. Measurements in this study was performed using a questionnaire based on the variables used. Data were analyzed using classical assumption test and multiple regression analysis. Based on the analysis and discussion of the quality of service showed that the appearance of Pharmacy, Hospitality Officer, Drug Information Service at the pharmacy, Availability of Medicines in Pharmacies, Pharmacy Services and Speed affects customer satisfaction in using Pharmacy Fitri Temanggung.Keywords: Service Quality, Appearance Pharmacy, Hospitality Officer, Service Drug Information, Drug Availability, Speed Service, Customer Satisfaction.